2013
DOI: 10.1371/journal.pone.0072638
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble of Gene Signatures Identifies Novel Biomarkers in Colorectal Cancer Activated through PPARγ and TNFα Signaling

Abstract: We describe a novel bioinformatic and translational pathology approach, gene Signature Finder Algorithm (gSFA) to identify biomarkers associated with Colorectal Cancer (CRC) survival. Here a robust set of CRC markers is selected by an ensemble method. By using a dataset of 232 gene expression profiles, gSFA discovers 16 highly significant small gene signatures. Analysis of dichotomies generated by the signatures results in a set of 133 samples stably classified in good prognosis group and 56 samples in poor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Moreover, in breast and prostate cancers, AKT can also be activated by other RTKs through TRAF6-mediated signaling (8,9). In this study, we describe a novel function of DCBLD2, an orphan membrane receptor that has an unclear role in human cancers (15)(16)(17)39), in mediating EGFR/AKT-driven tumorigenesis. We show that DCBLD2 is expressed at high levels in clinical samples of GBMs and HNCs.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, in breast and prostate cancers, AKT can also be activated by other RTKs through TRAF6-mediated signaling (8,9). In this study, we describe a novel function of DCBLD2, an orphan membrane receptor that has an unclear role in human cancers (15)(16)(17)39), in mediating EGFR/AKT-driven tumorigenesis. We show that DCBLD2 is expressed at high levels in clinical samples of GBMs and HNCs.…”
Section: Discussionmentioning
confidence: 89%
“…However, it is of note that our results should be considered exploratory because of the limited sample size of the study. We and others have identified that high expression of CD73 in tumor cells can be used as an independent prognostic biomarker for human CRC [19,22,23]. Thus, the tumoral expression levels of CD73 and CD39 were combined to evaluate the prognostic value in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…DCBLD2 and GSDMD have considerable tumor-specific effects, but their roles.in PDAC development remain unclear. DCBLD2 is overexpressed in glioblastoma, colorectal cancer, and lung cancer [39][40][41], and it is strongly associated with tumor migration and invasion. GSDMD plays an important role in the regulation of pyroptosis and sensitivity to cancer therapy [42].…”
Section: Discussionmentioning
confidence: 99%